RESTLESS LEGS SYNDROME IN THE CONTEXT OF CHRONIC KIDNEY DISEASE (CLINICAL CASE) - Raimova M.M., Mukhamedsaidova I.A. (Central Asian Journal of Medicine, 2025)
Chronic kidney disease is a condition characterized by a long-term decline in kidney function. It is marked by damage to kidney tissue or insufficient kidney function. Many publications extensively cover the development of secondary restless legs syndrome against the background of chronic kidney disease, the causative factors, and the course of the disease. In the clinical case presented below, restless legs syndrome developed as a result of chronic kidney disease, the disease progression, and the regression of symptoms over a short period due to complex treatment are described in detail.